2021
DOI: 10.1038/s41380-021-01128-8
|View full text |Cite
|
Sign up to set email alerts
|

White matter changes in psychosis risk relate to development and are not impacted by the transition to psychosis

Abstract: Subtle alterations in white matter microstructure are observed in youth at clinical high risk (CHR) for psychosis. However, the timing of these changes and their relationships to the emergence of psychosis remain unclear. Here, we track the evolution of white matter abnormalities in a large, longitudinal cohort of CHR individuals comprising the North American Prodrome Longitudinal Study (NAPLS-3). Multi-shell diffusion magnetic resonance imaging data were collected across multiple timepoints (1-5 over 1 year) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 66 publications
2
19
2
Order By: Relevance
“…Finding a reliable biomarker or at least achieving some biomarker-informed improvement in prognostic accuracy could revolutionize early recognition and intervention. There is an ongoing discussion of whether the transition may be marked by dramatic changes in WM microstructure or rather follows a more subtle pattern ( Di Biase et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finding a reliable biomarker or at least achieving some biomarker-informed improvement in prognostic accuracy could revolutionize early recognition and intervention. There is an ongoing discussion of whether the transition may be marked by dramatic changes in WM microstructure or rather follows a more subtle pattern ( Di Biase et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the gradual development of myelin, deficient production and misplacement of oligodendrocytes in the brain could lead to uneven myelination and strengthening of axonal pathways in schizophrenia. In general, the current evidence suggests that schizophrenia is associated with persistent developmental alterations in brain connectivity that could be caused by aberrant axonal pathfinding or myelination [74,75]. However, these changes could also arise from remodeling of connections later in adolescence, particularly in somatosensory and prefrontal cortices [103].…”
Section: Trends In Neurosciencesmentioning
confidence: 94%
“…In support of the early developmental origin of these alterations, individuals with familial risk for ASD have been found to display a caudal shift in thalamocortical wiring in infancy [72], whereas toddlers with high risk for schizophrenia reportedly exhibit hypoconnectivity in the thalamo-PFC tract [73]. Longitudinal studies have observed alterations in brain white matter tracts in individuals at high risk for psychosis persisting from childhood to adulthood, with no dramatic changes associated with transition to psychosis [74,75] (Box 2). Thus, the risk for psychosis appears to be linked to developmentally established structural alterations in brain connectivity.…”
Section: Brain Connectivity In Schizophreniamentioning
confidence: 99%
“…If dysregulated or “hyperplastic” critical period processes are occurring in early phases of illness, they are happening concurrently with dynamic macro-scale structural brain changes that signal a devolving cortex, consistent with over-exuberant synaptic sculpting as the brain attempts to shape its representations to an environment with unreliable statistics and/or is responding to increased stress and inflammation. High-risk individuals who develop psychosis have greater rates of cortical atrophy and reductions in the fractional anisotropy of white matter than those who don’t over the one-year period prior to onset of illness [ 161 , 162 ]. In animal models, sensory deprivation, sensory noise, deleterious environments, and social isolation all impact cortical integrity and myelination [ 163 ].…”
Section: Dysregulated Experience-dependent Plasticity Processes Inter...mentioning
confidence: 99%